Surrogacy Understanding Types and Exploring the Islamic Perspective - Dr Hareem Muzammil; Mian Muhammad Ali awais; Hansa (International Research Journal of Arabic and Islamic Studies, 2024)
This assignment comprehensively explores the intricate topic of surrogacy, covering its diverse types and intricacies, while concurrently delving into the Islamic perspective on this assisted reproductive practice. Beginning with an introduction to the concept and its significance, the assignment proceeds to dissect traditional and gestational surrogacy, distinguishing between altruistic and commercial motivations. Legal and ethical dimensions are examined globally, leading to a focused analysis of the Islamic stance on surrogacy. The assignment also investigates the varying positions of Islamic countries, shedding light on regulations and cultural responses. Through case studies and a thorough examination of sources, this assignment aims to provide a nuanced understanding of surrogacy, considering both its global landscape and its specific implications in Islamic contexts.